A Model Predictive Motion Cueing Strategy for a 5-Degree-of-Freedom Driving Simulator with Hybrid Kinematics - Biemelt, Patrick; Henning, Sven; Rüddenklau, Nico; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the Driving Simulation Conference Europe VR (DSC))

Modellbasierter Entwurf intelligenter mechatronischer Systeme mithilfe semantischer Technologien - Oestersötebier, Felix

A Reinforcement Learning Strategy for the Swing-Up of the Double Pendulum on a Cart - Hesse, Michael; Timmermann, Julia; Hüllermeier, Eyke; Trächtler, Ansgar (Procedia Manufacturing)
The effective control design of a dynamical system traditionally relies on a high level of system understanding, usually expressed in terms of an exact physical model. In contrast to this, reinforcement learning adopts a data-driven approach and constructs an optimal control strategy by interacting with the underlying system. To keep the wear of real-world systems as low as possible, the learning process should be short. In our research, we used the state-of-the-art reinforcement learning method PILCO to design a feedback control strategy for the swing-up of the double pendulum on a cart with remarkably few test iterations at the test bench. PILCO stands for “probabilistic inference for learning control” and requires only few expert knowledge for learning. To achieve the swing-up of a double pendulum on a cart to its upper unstable equilibrium position, we introduce additional state restrictions to PILCO, so that the limited cart distance can be taken into account. Thanks to these measures, we were able to learn the swing up at the real test bench for the first time and in only 27 learning iterations.

Virtuelle Inbetriebnahme eines Fertigungszentrums - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Tag des System Engineering)

Modellbasierte Untersuchung der Zuverlässigkeit algorithmisch bestimmter kritischer Stellen in Straßennetzwerken - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Fast hybrid position / force control of a parallel kinematic load simulator for 6-DOF Hardware-in-the-Loop axle tests - Kohlstedt, Andreas; Traphöner, Phillip; Olma, Simon; Jäker, Karl-Peter; Trächtler, Ansgar (2017 IEEE International Conference on Advanced Intelligent Mechatronics (AIM))

Nonlinear Model Predictive Control with Discrete Mechanics and Optimal Control - Xu, Ke; Timmermann, Julia; Trächtler, Ansgar (Proc. Advanced Intelligent Mechatronics (AIM))

Swing-up of the moving double pendulum on a cart with simulation based LQR-Trees - Xu, Ke; Timmermann, Julia; Trächtler, Ansgar (Proc. 20th IFAC World Congress)

Networked Driving Simulation for Future Autonomous and Cooperative Vehicle Systems - Abdelgawad, Kareem; Henning, Sven; Biemelt, Patrick; Gausemeier, Sandra; Trächtler, Ansgar (VDI/VDE (AUTOREG 2017))

Model-Based Design of Self-Correcting Forming Processes - Krüger, Martin; Borsig, Michael; Damerow, Ulf-Hendrik; Gräler, Manuel; Trächtler, Ansgar (Math for the Digital Factory)

Universelle Entwicklungs- und Prüfumgebung für mechatronische Fahrzeugachsen - Traphöner, Phillip; Olma, Simon; Kohlstedt, Andreas; Jäker, Karl-Peter; Trächtler, Ansgar (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017)

Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) - Gausemeier, Jürgen; Bodden, Eric; Dressler, Falko; Dumitrescu, Roman; Meyer auf der Heide, Friedhelm; Scheytt, Christoph; Trächtler, Ansgar

A Holistic Approach for Virtual Commissioning of Intelligent Systems - Henke, Christian; Michael, Jan; Lankeit, Christopher; Trächtler, Ansgar (Systems Conference 2017)

Dynamische Prozessplanung im Smart Home auf Basis von Mutliagentensystemen - Michael, Jan; Hellweg, Alina; Henke, Christian; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Kinematics-based force/position control of a hexapod in a HiL axle test rig - Kohlstedt, Andreas; Olma, Simon; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (17. Internationales Stuttgarter Symposium, Band 2)

Modellprädiktive Vorsteuerung für einen kinematisch redundanten hybridkinematischen Mechanismus im Industrieumfeld - Rüting, Arne Thorsten; Block, Eduard; Trächtler, Ansgar (Fachtagung Mechatronik 2017)

Adaptive Sigma-Punkte- Filter-Auslegung zur Zustands- und Parameterschätzung an Black-Box- Modellen - Schweers, Christoph

Innovative Suspensions for Caterpillar Vehicles - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Russian Engineering Research)

Methodology for Determining Critical Locations in Road Networks based on Graph Theory - Henning, Sven; Biemelt, Patrick; Abdelgawad, Kareem; Gausemeier, Sandra; Trächtler, Ansgar (IFAC World Congress 2017)

Scientifc Automation: Hochpräzise Analysen direkt in der Steuerung - Papenfort, Josef; Bause, Fabian; Frank, Ursula; Strughold, Sebastian; Trächtler, Ansgar; Bielawny, Dirk; Henke, Christian (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Reliable Multipath Communication Approach for Internet-based Cyber-physical Systems - Elattar, Mohammad; Jasperneite, Jürgen; Trächtler, Ansgar; et, al (26th IEEE International Symposium on Industrial Electronics (ISIE))

Flachheitsbasierte Positionsregelungen für Parallelkinematiken am Beispiel eines hochdynamischen Hexapoden - Knoop, Sarah

Mechanisch - mathematisches Modell eines Kettenfahrzeuges für die Entwicklung innovativer Antriebs- und Federungssysteme (auf russ.) - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Interbranch Scientific and Technical Magazine «Vestnik Mashinostroeniya»)

Integrierte, selbstoptimierende Fahrdynamikregelung mit Einzelradaktorik - Reinold, Peter

Indirect Force Control in Hardware-in-the-Loop Simulations for a Vehicle Axle Test Rig - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (14th International Conference on Control, Automation Robotics & Vision (ICARCV))

Feature Model Based Interface Design for Development of Mechatronic Systems

PROFINET-Implementierung im Rahmen der Entwicklung eines intelligenten, selbstlernenden Teigkneters - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Oestersötebier, Felix; Wessels, Sebastian (Virtuelle Instrumente in der Praxis 2016)

A HRRN based scheduling for FMS and RMS with networked control and product-intelligence - Bertelsmeier, Fabian; Pollmann, Jan; Trächtler, Ansgar (Inproceedings of the IEEE IECON 2016)

Model Predictive Feedforward Compensation for Control of Multi Axes Hybrid Kinematics on PLC - Rüting, Arne Thorsten; Blumenthal, Lars Martin; Trächtler, Ansgar (Proceedings of IEEE IECON 2016)

Nichtlineare Zustandsregelung mit Sliding-Mode-Beobachter für einen Achsprüfstand mit hydraulischem Hexapoden - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Trächtler, Ansgar (GMA Fachausschuss 1.40 "Theoretische Verfahren der Regelungstechnik")

Substructuring and Control Strategies for Hardware-in-the-Loop Simulations of Multiaxial Suspension Test Rigs - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 7th IFAC Symposium on Mechatronic Systems)

Study of a rail-bound parallel robot concept with curvilinear closed-path tracks - Bielawny, Dirk; Wang, Peng; Trächtler, Ansgar (Proceedings of 7th IFAC Symposium on Mechatronic Systems & 15th Mechatronics Forum International Conference)

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Graeler, Manuel; Henke, Christian; Hessel-von Molo, Mirko; Dellnitz, Michael; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Design and Implementation of Intelligent Control Software for a Dough Kneader - Oestersötebier, Felix; Traphöner, Phillip; Reinhart, Felix; Wessels, Sebastian; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Approach for an Integrated Model-Based System Design of Intelligent Dynamic Systems Using Solution and System Knowledge - Oestersötebier, Felix; Abrishamchian, Farisoroosh; Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Model-based method for the accuracy analysis of Hardware-in-the-Loop test rigs for mechatronic vehicle axles - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Disturbance Observer Design for Utilizing of Time-delayed Vision Measurements in High Dynamic Systems - Wang, Shuo; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Development and design of intelligent product carriers for ﬂexible networked control of distributed manufacturing processes - Bertelsmeier, Fabian; Schöne, Stefan; Trächtler, Ansgar (Inproceedings of the IEEE 24th Mediterranean Confernce on Control and Automation (MED))

Control of a hydraulic hexapod for a Hardware-in-the-Loop axle test rig - Kohlstedt, Andreas; Olma, Simon; Flottmeier, Sarah; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (at-Automatisierungstechnik)

Consistency Analysis for Requirements, Functions, and System Elements - Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (IEEE Systems Conference)

Modellbildung und Simulation im Kontext des Systems Engineering - Michael, Jan; Holtkötter, Jens; Henke, Christian; Trächtler, Ansgar (ASIM-Treffen STS/GMMS 2016)

Implementing intelligent technical systems into smart homes by using model based systems engineering and multi-agent systems - Michael, Jan; Hillebrand, Michael; Wohlers, Benedict; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Renewable Energy and Power Quality Journal (RE&PQJ) 16)

Precision Control of SMA Actuators with a Real Time Model-Based Controller and Extended VSC - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IFAC-PapersOnLine)

Regelungstechnik - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

A model extended temperature and strain controller modulated with PWM for precision position control of shape memory alloy actuators - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IEEE International Conference on Advanced Intelligent Mechatronics AIM)

Multidomänenmodell zur Optimierung der Hydraulik eines Raupenlaufwerks für Landmaschinen - Kruse, Daniel; Warkentin, Andreas P.; Krüger, Martin; Trächtler, Ansgar; Rackow, Sascha (Proc. 4. Internationales Commercial Vehicle Technology Symposium)

Consensus-based local information coordination for the networked control of the autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Complex & Intelligent Systems)

Simultaneous path planning and trajectory optimization for robotic manipulators using discrete mechanics and optimal control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Verbesserte Schätzung von Fahrdynamikgrößen durch Modellierung der Fahrwerks-und Lenkkinematik - Renninger, Johannes; Trächtler, Ansgar (at-Automatisierungstechnik)

A Novel Approach Using Model Predictive Control to Enhance the Range of Electric Vehicles - Eckstein, Julian; Lüke, Christopher; Brunstein, Frederik; Friedel, Patrick; Köhler, Ulrich; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering, SysInt 2016)

Feature Model Approach For Managing Variability of Dynamic Behavior Models in Mechatronic Systems - Abrishamchian, Farisoroosh; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition)

Decentralized Controller Reconﬁguration Strategies for Hybrid System Dynamics based on Product-Intelligence - Bertelsmeier, Fabian; Trächtler, Ansgar (20th IEEE International Conference on Emerging Technologies and Factory Automation)

Flexible Operation Workflow of a Driving Simulation Center for ADAS Development - Abdelgawad, Kareem; Hassan, Bassem; Kohlstedt, Andreas; Stöcklein, Jörg; Berssenbrügge, Jan; Grafe, Michael; Gausemeier, Sandra; Jäker, Karl-Peter; Trächtler, Ansgar (New Developments in Driving Simulation Design and Experiments)

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin; Trächtler, Ansgar (at-Automatisierungstechnik)

Produkt- und lastabhängiges dezentrales Motormanagement für die Fördertechnik: Anforderungen, Design und Applikation - Bertelsmeier, Fabian; Vathauer, Marc; Henke, Christian; Vathauer, Karl-Ernst; Trächtler, Ansgar (Automation 2015)

Modelling the Constitutive Behaviour of Martensite and Austenite in Shape Memory Alloys Using Closed-Form Analytical Continuous Equations - Pai, Arathi; Niendorf, Thomas; Krooß, Philipp; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (7th ECCOMAS Thematic Conference on Smart Structures and Materials - SMART)

Intelligente Biegeverfahren - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Hesse, Marc; Homberg, Werner; Trächtler, Ansgar; Jungeblut, Thorsten (wt Werkstattstechnik online)

A Modular Architecture of an Interactive Simulation and Training Environment for Advanced Driver Assistance Systems - Abdelgawad, Kareem; Hassan, Bassem; Berssenbrügge, Jan; Stöcklein, Jörg; Grafe, Michael (International Journal On Advances in Software)

Design and Control of Cooperative Ball Juggling Delta Robots without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (Robotica)

Path Planning and Trajectory Optimization of Delta Parallel Robot - Shareef, Zeeshan

Automatische Ableitung geometrischer Eigenschaften von Bauteilen aus dem 3-D-Polygonmodell - Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Visualisierung von Scheinwerfersystemen für das Virtual Prototyping von lichtbasierten Fahrerassistenzsystemen - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph; Stöcklein, Jörg; Grafe, Michael (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Anbindung des Virtuellen Prototypen an die Partialmodelle intelligenter technischer Systeme - Berssenbrügge, Jan; Wiederkehr, Olga; Jähn, Claudius; Fischer, Matthias (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Entwicklung eines prädiktiven Motion-Cueing-Verfahrens für den ATMOS-Fahrsimulator - Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Online-Rekonﬁguration hybrider Regelkreise in Abhängigkeit variierender Produkteigenschaften - Bertelsmeier, Fabian; Engelmeier, Tobias; Trächtler, Ansgar (Tagungsband Mechatronik 2015)

Systematische Wahl der Modellierungstiefe im Entwurfsprozess mechatronischer Systeme am Beispiel eines Geldautomaten - Lochbichler, Matthias; Lankeit, Christopher; Trächtler, Ansgar; Landwehr, Martin; Hoischen, Ludger (Tagungsband Mechatronik)

Tutorenprogramm und Vertiefungsberatung stellen Weichen in entscheidenden Phasen des Student Life-Cycles in Maschinenbaustudiengängen - Koke, Isabel; Dibblee, Katharina; Hankeln, Frederik; Seidel, Stefan; Trächtler, Ansgar; Schmid, Hans-Joachim (44. Jahrestagung der Deutschen Gesellschaft für Hochschuldidaktik - Hochschuldidaktik im Dialog, Paderborn)

Modellbasierte Mehrzieloptimierung zur Integration von Hausgeräten in SmartGrids - Michael, Jan; Hillebrand, Michael; Dumitrescu, Roman; Henke, Christian; Trächtler, Ansgar (VDI Mechatronik 2015 Tagungsband)

Safe trajectory planning for autonomous intersection management by using vehicle to infrastructure communication - Wuthishuwong, Chairit; Trächtler, Ansgar; Bruns, Torsten (EURASIP Journal on Wireless Communications and Networking)

Challenges in Requirements Engineering for Mechatronic Systems – Problem Analysis and First Approach - Lankeit, Christopher; Lochbichler, Matthias; Trächtler, Ansgar (Jurnal Teknologi)

From Goals to Systems via Technical Requirements and Physical Models - Design of an Intelligent Cash Handling System - Lankeit, Christopher; Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar; Landwehr, Martin (Proceedings)

Real-Time Compatible Phenomenological Modelling of the Austenitic Phase in Shape Memory Alloys as an Example for Modelling of Materials with Repeatable Non-Linear Characteristics - Pai, Arathi; Trächtler, Ansgar; Schaper, Mirko (IFAC 1st Conference on Modelling, Identification and Control of Nonlinear Systems - MICNON)

Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, Christian; Wang, Zheng; Koke, Isabel; Tröster, Thomas (20th International Conference on Composite Materials, Copenhagen)

Virtual Commissioning by Means of an Adaptive Selection of the Modeling Depth - Frieben, Tanja; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE14, Montreal, Québec, Canada)

Methodology for a Partly Automated Parameter Identification for the Validation of Multi-Domain Models - Kruse, Daniel; Schweers, Christoph; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Dynamic Behavior Models and their Modeling Depth in the Design Process of Mechatronic Systems - Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Ansätze zur Regelung eines elektronischen Lastemulators für die Hardware-in-the-Loop-Simulation von Antriebsreglern auf Leistungsebene - Kromov, Ivan; Deter, Matthias; Trächtler, Ansgar (SPS IPC Drives)

Optimal Trajectory Planning for Robotic Manipulators Using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Multi-Conference on Systems and Control (MSC) / 23rd Conference on Control Applications (CCA))

Analysis of high speed bending operations as basis for integrating self-correcting components to increase process reliability - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Homberg, Werner; Trächtler, Ansgar (Procedia Engineering 81)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin (Workshop GMA-Fachausschuss 1.30)

Subjective Evaluation of Different Motion Cueing Algorithms Implemented on ATMOS Driving Simulator - Al Qaisi, Imad; Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (Driving Simulation Conference 2014)

Consensus coordination for multiple autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Tagungsband 9. Dortmunder AutoTag)

Modellbasierte Analyse und regelungstechnische Maßnahmen zur Optimierung des Vereinzelungsvorgangs in Bankautomaten - Just, Viktor

Stability of the consensus in the network of multiple Autonomous Intersections Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 20th International Conference on Automation and Computing (ICAC))

Simultaneous Path Planning and Trajectory Optimization for Robotic Manipulators using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Consensus Coordination in the Network of Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 11th International Conference on Informatics in Control Automation and Robotics ICINCO)

Sliding Mode and Continuous Estimation Techniques for the Realization of Advanced Control Strategies for Parallel Kinematics - Flottmeier, Sarah; Olma, Simon; Trächtler, Ansgar (Proceedings of the 19th IFAC World Congress)

Control of Pareto Points for Self-Optimizing Systems with Limited Objective Values - Kessler, Jan Henning; Trächtler, Ansgar (The 19th IFAC World Congress)

Joint Selection Criterion for Optimal Trajectory Planning for Robotic Manipulators Using Dynamic Programming - Shareef, Zeeshan; Trächtler, Ansgar (19th IFAC World Congress)

Analyses of the stress-strain behaviour of SMAs under cyclical loading conditions – implementation of a novel phenomenological constitutive model - Pai, Arathi; Krooß, Philipp; Niendorf, Thomas; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (Posterbeitrag ICOMAT - International Conference on Martensitic Transformations, Juli 2014, Bilbao, Spanien)

Concept for a self-correcting sheet metal bending operation

Design and Control of a Vertical Ball Juggling Delta Robot without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (13th International Conference on Intelligent Autonomous Systems)

Configuration of Mechatronic Systems Using Feature Models - Abrishamchian, Farisoroosh; Trächtler, Ansgar (2nd International Conference on System-Integrated Intelligence)

Selbstkorrigierende Biegeprozesse in der Umformtechnik

Continuous Objective-based Control for Self-Optimizing Systems with Changing Operation Modes - Kessler, Jan Henning; Krüger, Martin; Trächtler, Ansgar (13th European Control Conference (ECC))

Semantische Technologien im Entwurf mechatronischer Systeme: Effektiver Austausch von Lösungswissen in Branchenwertschöpfungsketten - Gausemeier, Jürgen; Trächtler, Ansgar; Schäfer, Wilhelm; Anacker, Harald; Bauer, Frank; Borcherding, Holger; Dziwok, Stefan; Frank, Ursula; Herden, Rudolf; Hoppe, Gerd; Just, Viktor; Kiele-Dunsche, Markus; et al.

Model-based design of self-correcting forming processes - Krüger, Martin; Borsig, Michael; Schaermann, Waldemar (KoMSO Challenge Workshop Math for the Digital Factory)